Весняні ефемероїди флори Кавказу в природі та культурі Національного ботанічного саду імені М.М. Гришка НАН України - Didenko, S. Ja. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2017)
Objective – to increase the efficiency of introduction of rare Caucasus flora spring ephemeroids (Cyclamen coum Rehb., Helleborus caucasicus A. Braun, Erytronium caucasicum Woronow, Ornithogalum arcuatum Stev., O. ponticum Zahar.) at M.M. Gryshko National Botanical Garden of NАS of Ukraine. Material and methods. In 2011 and 2012 years expeditions were made the trip to the Caucasus for study of natural populations of these species. Comparison of natural and introduction populations, that evolved over several decades in M.M. Gryshko National Botanical Garden of NАS of Ukraine is carried out. Results. All studied species grow well, blossom and bear fruit, formed a stable population of introduction. Only C. coum require artificial support. Conclusion. The study of natural populations allows not only to compare growth conditions and the state of introduction populations from their natural counterparts, but also make the introduction of more effective.